AB0022 Modulation of Treg Stability and Function by Inhibition of IL-1beta. (15th July 2016) - Almanzar, G.; Greupner, M.; Morris, P.; Hoefner, K.; El Hajj, N.; Haaf, T.; Schmalzing, M.; Haas, J.P.; Tony, H.P.; Prelog, M.
Abstract : Background: High plasticity was described for Th1 and Th17 cells depending on the local cytokine milieu and regulation by Tregs. Pathogen-induced human Th17 cells and Tregs are strongly regulated by IL-1beta. So far, the influence of IL-1beta on FoxP3 methylation and stability of the Treg lineage has not been investigated. Further, whether inhibition of IL-1beta and its receptor is able to promote FoxP3 demethylation and to conserve Treg functions, such as suppression of Th17 and Th1 functions, has not been assessed in healthy humans, as well as in patients with autoimmune arthritis. Objectives: Thus, the present study aimed to investigate in vitro nTreg and iTreg functions in lymphocytes obtained from stored routine blood samples of patients with juvenile idiopathic arthritis (JIA) or rheumatoid arthritis (RA) in different disease activity states. Methods: Proportions of peripheral nTregs and cultured iTregs from stored routine blood samples taken from JIA, RA patients and healthy, age-matched controls (HC) and intracellular cytokine production were analyzed by flow cytometry. Suppressive function of iTregs under in vitro inhibition of IL-1beta was studied by suppression assays. FOXP3 expression and methylation were analyzed by quantitative PCR and bisulfite pyrosequencing. Results: Lower proportions of nTregs were found in samples of JIA patients with acute disease flare (mean 2.3% of CD4+ T cells) compared to HC (4.1%) (p<0.001). Using IL-1beta and other Th17-stimulating cytokines, proportions of induced iTregs were similar between JIA samples with acute disease flare (mean 34.6% of CD4+ T cells) and healthy children (38.1%), but lower in remission (13.2%) (p<0.001). Proportions of iTregs were markedly induced by blockade of IL-1beta in both JIA (mean 78.1% of CD4+ T cells) and HC (84.0%) compared to cells without blockade (p<0.01). IL-1beta blockade reduced proliferation of effector T cells by induction of suppressive function of iTregs in both JIA (suppression from 55.1% to 34.2% proliferating effectors) and HC (from 48.2% to 31.8%) (p<0.001). Intracellular IL-10 production was not influenced by blockade of IL-1beta. Conclusions: Induction of Tregs seems to be different depending on disease activity status in autoimmune arthritis. DNA methylation at the FOXP3 promoter and enhancer regions may influence expression of FoxP3 in Tregs and, thus, modify their phenotype. Although IL-10 was not markedly influenced by IL-1beta-dependent mechanisms, our findings indicate that suppressive iTreg functions may be restored by selective blockade of IL-1beta. Disclosure of Interest: None declared